(27^-2/3)^1/2 s equal to

Given: \(((27)^-{\frac{2}{3}})^{\frac{1}{2}}\) \(((27)^-{\frac{2}{3}}*{\frac{1}{2}})\) = \((27)^-{\frac{1}{3}}\) =\((\frac{1}{27})^{\frac{1}{3}}\) = \((\frac{1}{3^{3}})^{\frac{1}{3}}\) = \((\frac{1}{3^{3}*\frac{1}{3}})\) = 1/3

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question